2017
DOI: 10.1093/jnci/djx201
|View full text |Cite
|
Sign up to set email alerts
|

Lung, Bladder, and Kidney Cancer Mortality 40 Years After Arsenic Exposure Reduction

Abstract: Lung, bladder, and kidney cancer mortality due to arsenic exposure have very long latencies, with increased risks manifesting 40 years after exposure reduction. Our findings suggest that arsenic in drinking water may involve one of the longest cancer latencies for a human carcinogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(56 citation statements)
references
References 38 publications
1
48
0
1
Order By: Relevance
“…One thing is certain however: studying environmental exposures solely at the time of symptom onset is unlikely to reveal all that needs to be known, since the neurodegenerative disease process probably began years prior to the onset of clinical symptoms. We have no empirical evidence regarding the "incubation period" of ALS, but work in cancer may be relevant, where, for instance, arsenic has been reported to increase the incidence of bladder cancer only after 10 years of exposure and the incidence continued to rise for 20 years after termination of exposure [10].…”
Section: Temporal Considerations In Exposures To Chronic Environmentamentioning
confidence: 99%
“…One thing is certain however: studying environmental exposures solely at the time of symptom onset is unlikely to reveal all that needs to be known, since the neurodegenerative disease process probably began years prior to the onset of clinical symptoms. We have no empirical evidence regarding the "incubation period" of ALS, but work in cancer may be relevant, where, for instance, arsenic has been reported to increase the incidence of bladder cancer only after 10 years of exposure and the incidence continued to rise for 20 years after termination of exposure [10].…”
Section: Temporal Considerations In Exposures To Chronic Environmentamentioning
confidence: 99%
“…The other major source is As‐contaminated air and food caused by combustion high As‐containing coal in unventilated indoor stoves for cooking, which has been exclusively reported in Guizhou province in China in 2002 year 8 . Epidemiological studies have shown that there is high prevalence of arsenicosis such as skin, 9,10 liver, 11 kidney, 12 lung, 13 and bladder damage 14 . Liver, as one of the important target organs of arsenic toxicity, exhibits an increase of hepatocyte apoptosis in hepatic tissues and primary hepatocytes 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Chronic exposure to inorganic arsenic via drinking water is associated with increased risk for various human cancers, as well as diseases of myriad body systems that include cardiovascular, neurologic, endocrine, integumentary and respiratory (García-Esquinas et al, 2013;Hong, Song, & Chung, 2014;Martinez, Vucic, Becker-Santos, Gil, & Lam, 2011;Putila & Guo, 2011;Smith et al, 1992;Smith et al, 2006;Tyler & Allan, 2014). Focusing on the respiratory system, studies in arsenic-exposed populations in northern Chile documented increased risk for early death from lung cancer and obstructive pulmonary disease (Smith et al, 2018;Smith, Goycolea, Haque, & Biggs, 1998). Furthermore, arsenic exposure from drinking water in Bangladesh has been linked to dyspnea and pneumonia (George et al, 2015;Pesola et al, 2012).…”
Section: Introductionmentioning
confidence: 99%